Niche differentiation of bacteria and fungi in carbon and nitrogen cycling of different habitats in a temperate coniferous forest: A metaproteomic approach. (April 2021) - Starke, Robert; Mondéjar, Rubén López; Human, Zander Rainer; Navrátilová, Diana; Štursová, Martina; Větrovský, Tomáš; Olson, Heather M.; Orton, Daniel J.; Callister, Stephen J.; Lipton, Mary S.; Howe, Adina; McCue, Lee Ann; et al.
Abstract: Temperate coniferous forests sustain the highest levels of biomass of all terrestrial ecosystems and belong to the major carbon sinks on Earth. However, the community composition and its functional diversity depending on the habitat have yet to be unveiled. Here, we analyzed the proteomes from litter, plant roots, rhizosphere, and bulk soil in a temperate coniferous forest at two time points to improve the understanding of the interplay between bacterial and eukaryotic communities in different habitats. Our metaproteomic approach yielded a total of 139, 127 proteins that allowed to differentiate the contribution of microbial taxa to protein expression as well as the general functionality based on KEGG Orthology in each habitat. The pool of expressed carbohydrate-active enzymes (CAZymes) was dominated by fungal proteins. While CAZymes in roots and litter targeted mostly the structural biopolymers of plant origin such as lignin and cellulose, the majority of CAZymes in bulk and rhizosphere soil targeted oligosaccharides, starch, and glycogen. Proteins involved in nitrogen cycling were mainly of bacterial origin. Most nitrogen cycling proteins in litter and roots participated in ammonium assimilation while those performing nitrification were the most abundant in bulk and rhizosphere soil. Together, our results indicated niche differentiation of the microbial involvement in carbon and nitrogen cycling in a temperate coniferous forest topsoil. Graphical abstract: Image 1 Highlights: Habitats in a temperate coniferous forest differ in their protein composition. Bacteria dominated N cycling while fungi contributed more to C cycling. CAZymes in roots and litter targeted mostly plant structural biopolymers. Ammonium assimilation in litter/roots and nitrification in rhizosphere/soil.